Hypothalamic Astrocytes Respond to Gastric Mucosal Damage Induced by Restraint Water-Immersion Stress in Rat - Sun, Haiji; Li, Ruisheng; Xu, Shiguo; Liu, Zhen; Ma, Xiaoli (Frontiers in Behavioral Neuroscience, 2016)
Restraint water-immersion stress (RWIS), a compound stress model, includes both psychological and physical stimulation. Studies have shown that neurons in the hypothalamus are involved in RWIS, but the role of astrocytes and the interactions between astrocytes and neurons in RWIS are not clear. Here, we tested our hypothesis that hypothalamus astrocytes are involved in RWIS and interact with neurons to regulate gastric mucosal damage induced by RWIS. The expression of Glial fibrillary acidic protein (GFAP) and c-Fos in the paraventricular nucleus (PVN) and supraoptic nucleus (SON) significantly increased following the RWIS. GFAP and c-Fos expression are similar in the temporal pattern, peaked at 1h after the RWIS, then reduced gradually, and reached a maximal level again at 5h , which show “double-peak” characteristics. Intracerebroventricular administration of astroglial toxin L-a-aminoadipate (L-AA) and c-fos antisense oligodeoxy nucleotides (ASO) both decreased RWIS-induced gastric mucosal damage. Results by immunohistochemistry assay revealed that both L-AA and ASO decreased the activation of astrocytes and neurons in the hypothalamus by RWIS. These results showed that hypothalamus neuron-astrocyte “network” involved in gastric mucosal damage induced by RWIS. This study may offer theoretical basis for some novel therapeutic strategies for RWIS-induced gastric ulcers.